Strategi Mengatasi Problematika Mutu Pembelajaran Melalui Merdeka Belajar di Lembaga PAUD - Margareta Edis (Jurnal Wahana Literasi Pendidikan, 2026)
Early Childhood Education (ECCE) has an urgent role in the world of education. As an ECCE institution, its role is to ensure the quality of learning and educational services according to the standards and characteristics of child development. The problem that occurs today is in terms of quality or quality of learning. This type of research uses literature studies by collecting data through various book materials, articles, and research results related to research studies which are then analyzed. After conducting the screanning process, 20 articles and 4 books were selected as the final review. Data analysis techniques using content analysis methods aim to describe and infer the content of data sources. The result of deepening the literature is: there are still many ECCE products that have not met the established standards. In learning, it often happens that teachers do not carry out their roles and functions. Teachers explain a lot and still use a teacher-centered system. The assignment system tends to be passive so that children find it difficult to express opinions, lack of collaboration between teachers and children. As a result, teachers are unable to bring about change to develop creative learning models for early childhood. The strategy to overcome problems in the world of education is to improve the quality of learning. The government made a learning strategy by changing the child-centered curriculum, through Freedom to Play or Freedom to Learn.